Design and construction of high performance homes : building envelopes, renewable energies and integrated practice - Trubiano, Franca (London : Routledge, 2013)
' Both professionals and students are increasingly committed to achieving high-performance metrics in the design, construction and operation of residential buildings. This book responds to this demand by offering a comprehensive guide which features: architectural innovations in building skin technologies which make lighter more transparent buildings high performing ; energy-free architectural design principles and advances in building-integrated photovoltaics ; essential engineering principles, controls and approaches to simulation for achieving net zero ; the advantages of integrated design in residential construction and the challenges and opportunities it engenders ; detailed case studies of innovative homes which have incorporated low-energy design solutions, new materials, alternative building assemblies, digital fabrication, integrated engineering systems and operational controls. Divided into four parts, the book discusses the requisite AEC (Architecture, Engineering and Construction) knowledge needed when building a high-performance home. It also communicates this information across four case studies, which provide the reader with a thorough overview of all aspects to be considered in the design and construction of sustainable homes. With contributions from experts in the field, the book provides a well-rounded and multi-faceted approach. This book is essential reading for students and professionals in design, architecture, engineering (civil, mechanical and electrical), construction and energy management.'--Publisher's website.
Editor' Preface: High Performance Homes: Metrics, Ethics and Design / anca Trubiano -- Introduction: Household Power: How Much is Enough? / William W Braham. -- Part 1: Building Envelopes, New Materials and Architectural Design. Energy Free Architectural Design - The Case of PassivHaus and Double Skin Facades / Franca Trubiano ; Translucent Building Skins - Advancing the Technology of Light Transmission / Franca Trubiano ; Responsive Building Envelopes: Characteristics and Evolving Paradigms / Kathy Velikov and Geoffrey Thun ; Nano-Materials + Super Insulator = Aerogel / Franca Trubiano. -- Part 2: Renewable Energies, Building Systems and Simulations. The Design Integration of Renewable Energies / Franca Trubiano and Russell Gentry ; Systems Integrated Photovoltaics, SIPV / Jeffrey Brownson ; Building Systems, Controls and Automation / Russell Gentry ; Building Performance and Computational Simulation / Yun Kyu Yi. -- Part 3: Integrated Practice and Residential Construction. Integrated Project Delivery - Contracting for High Performance / Ryan Smith and Joerg Rugemer ; Energy and the Integrative Design Process, Defining the Team of Experts / Lisa Iulo ; The Construction of Low Energy Prefabricated Housing in Denmark / Anne Beim and Kasper Sanchez Vibaek ; From Modeling to Making, Parametric Design and Digital Fabrication / Tristan Al-Haddad. -- Part 4: High Performance Homes: Case Studies. LumenHaus and the Eclipsis Sun Control System / Robert Dunay, Joseph Wheeler and Robert Schubert ; Project Icarus: Optimizing Light and Energy in the Design of a Translucent Roof / Franca Trubiano ; North House: Climate Responsive Envelope and Control System / Geoffrey Thun and Kathy Velikov ; Modular Building; Three Scales/Three Strategies / Lisa Iulo.
Includes bibliographical references and index.
Keywords: Ecological houses -- Design and construction